Impacts of Diverse Natural Products on Honey Bee Viral Loads and Health - Dawn L. Boncristiani (MDPI AG, 2021)
Western honey bees (Apis mellifera), a cornerstone to crop pollination in the U.S., are faced with an onslaught of challenges from diseases caused by parasites, pathogens, and pests that affect this economically valuable pollinator. Natural products (NPs), produced by living organisms, including plants and microorganisms, can support health and combat disease in animals. NPs include both native extracts and individual compounds that can reduce disease impacts by supporting immunity or directly inhibiting pathogens, pests, and parasites. Herein, we describe the screening of NPs in laboratory cage studies for their effects on honey bee disease prevention and control. Depending on the expected activity of compounds, we measured varied responses, including viral levels, honey bee immune responses, and symbiotic bacteria loads. Of the NPs screened, several compounds demonstrated beneficial activities in honey bees by reducing levels of the critical honey bee virus deformed wing virus (DWV-A and-B), positively impacting the gut microbiome or stimulating honey bee immune responses. Investigations of the medicinal properties of NPs in honey bees will contribute to a better understanding of their potential to support honey bee immunity to fight off pests and pathogens and promote increased overall honey bee health. These investigations will also shed light on the ecological interactions between pollinators and specific floral food sources.